EFFECT OF EXERCISE DURING PREGNANCY AND DAM AGE ON MATERNAL BLOOD-CHEMISTRY AND FETAL GROWTH - Demello, MAR (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
In order to determine the effect of maternal exercise on maternal nutritional status and fetal growth, young (Y = 45-50 days old) Wistar rats were divided into 4 groups of 5 to 8 animals: control pregnant (CP), control non-pregnant (CNP), exercise-trained (swimming 1 h/day, 5 days/week, for 19 days) pregnant (TP) and exercise-trained non-pregnant (TNP). Four equivalent groups of adult rats (A - 90-100 days old) were also formed. Serum glucose, total protein, albumin, hematocrit and liver glycogen were determined in female rats and pups. There were no statistical differences in serum glucose, total protein and albumin levels, litter size ot birth weight among exercise-trained animals, controls and their respective pups. Hematocrit was significantly lower in pups of exercise-trained young rats than in all other groups (YCP = 38.6 +/- 3.0; YTP = 32.6 +/- 2.1; ACP = 39.0 +/- 2.5; ATP = 39.2 +/- 2.9%). Liver glycogen levels were lower in pregnant than in non-pregnant rats but similar in exercise-trained and control rats of the same age and physiological status (YCNP = 4.1 +/- 0.2; YCP = 2.7 +/- 0.9; YTNP = 4.9 +/- 0.8; YTP = 2.7 +/-0.4; ACNP = 6.1 +/- 0.6; ACP = 3.1 +/- 0.8; ATNP = 6.6 +/- 0.8; ATP = 2.2 +/- 0.9 mg/100 mg). We conclude that pups of adult female rats are spared from the effects of this kind of exercise training during pregnancy. on the other hand, it appears that maternal adaptations to exercise training in young rats are able to preserve only some aspects of pup metabolism.
Keywords: EXERCISE-TRAINING; FETAL GROWTH; MATERNAL-FETAL HOMEOSTASIS; EXERCISE DURING PREGNANCY